A Review of Parental Role on Risky Sexual Behaviour of Adolescents - Sharma, Sushil (Journal of Health Promotion, 2020)
Adolescence is a phase in human life which is characterized as the growing desire for sexual intercourse. Furthermore, the lack of knowledge on sexual health during this phase may result in risky sexual practices. So, parental monitoring is essential for this group of people. On this basis, I have conducted a review on parental monitoring of risky sexual behaviour of adolescents. While reviewing, accessible and eligible resources are consulted from PubMed, Hinari, Research Gate, etc up to November 2018. This review primarily focuses on how the parents monitor the probable risky sexual practices of their adolescent children. On the basis of existing literature, this review attempts to explore the growing risky practices of sexual behaviour among children without parental guidance.